(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study aimed to identify the effectiveness of an educational program based on the theory of the five minds in the academic achievement of fifth-grade students in biology and in developing their complex thinking. The researcher utilized both descriptive and experimental methods. An educational program was prepared that included educational objectives, teaching methods, appropriate strategies, activities, educational resources, and evaluative methods, which consisted of a teacher’s guide and a student’s book. The researcher purposefully selected secondary and middle schools in Dhi Qar Governorate / Al-Gharraf District to represent the research community, specifically choosing Al-Gharraf Martyrs Preparatory School. The Fifth Scientific Division (A) was randomly selected to represent the experimental group that teaches biology according to the educational program, consisting of 41 students, while the Fifth Scientific Division (B) represented the control group that teaches the same subject using the conventional method, also with 41 students. Thus, the research sample totaled 82 students. The researcher prepared two tools to measure the research variables: the first was an achievement test, in its final form consisting of 60 test items, for which the researcher verified validity, discrimination, and reliability; the second was a complex thinking test, which in its final form consisted of 33 test items, also verified for validity and reliability. The researcher used the Statistical Package for the Social Sciences (SPSS), version 27, to analyze the results. After performing statistical analyses, the researcher concluded that the experimental group outperformed the control group in both achievement tests and post-compositional thinking.